Reactive airways dysfunction syndrome following inhalation of hydrogen chloride vapor - Vanessa Simioni Faria; Soraya Abou El Hosn Cordero da Silva; Julio Flávio Meirelles Marchini (University of São Paulo, 2021)
Hydrogen chloride is available commercially as an anhydrous gas or an aqueous solution, hydrochloric acid. Exposure to this gas has been associated with the development of reactive airways dysfunction syndrome. However, there are few published reports. A 37-year-old woman developed progressive bronchospasm and acute respiratory failure after cleaning an enclosed space with an unknown concentration of hydrochloric acid gas from a cleaning substance. She had no prior history of asthma or atopy. Severe bronchospasm developed, leading to hypoxemia and diffuse interstitial infiltrates, necessitating orotracheal intubation and admission to the intensive care unit. Asthma-like symptoms such as cough, wheezing, and dyspnea; requiring bronchodilators, and repeated hospitalizations are persistent a year after the accident. Pulmonary function testing showed mild airflow obstruction.